The Effect of ELSA Speak Application on Students' Speaking Skill at Smk AKP Galang : Penelitian - Najunda Aulia; Amin, Teguh Satria (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to evaluate the extent to which the ELSA (English Language Speech Assistant) application is effective in improving students' English speaking skills, particularly in the aspects of pronunciation, intonation, and fluency. This study is conducted at SMK Swasta AKP Galang using a quantitative experimental method. Two classes of XI grade students are selected, namely XI RPL 1 (40 students) as the experimental group and XI RPL 2 (40 students) as the control group. Students' speaking ability is assessed through oral-based pre-tests and post-tests. The results of the statistical analysis show that the calculated t value (t₀) of 6.25 is higher than the t-table value of 1.699 at the 5% significance level with a degree of freedom (df) of 78. This finding indicates a statistically significant difference between the two groups. Thus, it can be concluded that the use of the ELSA Speak application is effective in improving students' speaking skills. This study also underscores the important role of mobile-based language learning technology (MALL) in supporting communicative teaching approaches as well as encouraging students' learning independence in the vocational education environment